Violencia conyugal y víctimas de la guerra: la valenciana Beatriz Martí y la troyana Andrómaca de Eurípides. - TERZOPOULOU, ANASTASIA (Scripta, 2020)
This paper develops the issue of violence against women in Ancient Greece and in the Crown of Aragon in the Late Middle Ages. Specifically, the cases analyzed have to do, on the one hand, with the violence committed against the Princess of Troy, Andromache, who, after the looting and fall of her homeland, has become a war captive, a concubine of the family that killed her husband and son; and, on the other, the case of the marital violence of the Valencian Beatriz Martí. Both women, despite the centuries that separate them, suffer injustices and pain, but they also have a person who helps and protects them: in the case of Andromache it is Peleus, the grandfather of its current owner; and, in the case of Beatriz, Queen Maria of Aragon.